Mass-Production and Characterization of Anti-CD20 Monoclonal Antibody in Peritoneum of Balb/c Mice - Leili Aghebati; Jalal Abdolalizadeh; Jafar Majidi; Behzad Baradaran; Koushan Sineh Sepehr; Fatemeh Zare Shahneh (Tabriz University of Medical Sciences, 2013)
Purpose: Monoclonal antibodies are important tools are used in basic research as well as, in diagnosis, imaging and treatment of immunodeficiency diseases, infections and cancers. The purpose of this study was to produce large scale of monoclonal antibody against CD20 in order to diagnostic application in leukemia and lymphomas disorders. Methods: Hybridoma cells that produce monoclonal antibody against human CD20 were administered into the peritoneum of the Balb/c mice which have previously been primed with 0.5 ml Pristane. After twelve days, approximately 7 ml ascetic fluid was harvested from the peritoneum of each mouse. Evaluation of mAb titration was assessed by ELISA method. In the present study, we describe a protocol for large scale production of MAbs. Results: We prepared monoclonal antibodies (mAbs) with high specificity and sensitivity against human CD20 by hybridoma method and characterized them by ELISA. The subclass of antibody was IgG2a and its light chain was kappa. Ascetic fluid was purified by Protein-A Sepharose affinity chromatography and the purified monoclonal antibody was conjugated with FITC and Immunofluorescence was done for confirming the specific binding. Conclusion: The conjugated monoclonal antibody could have application in diagnosis B-cell lymphomas, hairy cell leukemia, B-cell chronic lymphocytic leukemia, and melanoma cancer stem cells.